Synthesis of biochar and its metal oxide composites and application on next sustainable electrodes for energy storage devices - Bregadiolli, Bruna Andressa; Lustosa, Glauco Meireles Mascarenhas Morandi; Paulin, João Vitor [UNESP]; Bizzo, Waldir Antonio; Kubota, Lauro Tatsuo; Deng, Shuguang; Mazon, Talita (Elsevier, 2025)
Biochar materials have been applied in energy storage due to their unique properties, such as high storage of ions, high conductivity, chemical stability and ease of production. Combining it with the high specific capacitance could be a promising strategy to develop devices and improve the properties. Through a hydrothermal technique the biochar powders were synthesized from sugarcane biomass. An acid pretreatment was carried out before and after the graphitization process aiming to obtain carbon materials with high surface area and porosity. The morphological characterization reveals powders with pores of submicrometer diameter. For the pure biochar it was determined a superficial area of 477.66 m2.g−1 with a median pore size of 42.92 Å and a pore volume of 0.21 cm3.g−1. A carbon-based paste was then prepared to deposit on nickel foam and obtain the electrodes. In a 3-electrode system characterization, biochar has showed higher specific capacitance than the metal oxide composites due to higher surface area and higher medium pore diameter. It was calculated a resistance of 2.7 Ω, a capacitance of 446 mF.g−1, a power density of 46.2 W.kg−1 and an energy density of 1.8 W.h.kg−1. These results indicate the potential use of biochar-based electrodes with high electrical conductivity and improved surface area to obtain higher capacitance properties for development of advanced devices.